ШОҲ ҒАРИБ МИРЗО – ҒАРИБИЙ «ДЕВОН»ИНИНГ ЖАНР ХУСУСИЯТЛАРИ - Ҳалимов, С. (SCIENCE and SOCIETY, 2020)
The name Shokh Garib Mirzo is one of the princes of the Timurids today is hot well known to the readers. Despite the fact that it was known that Prince Shokh Garib Mirzo Garibiy was a poet and he had a collection of poems, that the representatives of science did not know about the existence of this collection. This Divan is currently kept in the library of Hamburg library of Germany.
Keywords: Shahgharib Mirza; Divan; Turkic-Uzbek gazalles; poetic divan; coup let; mukhammas; Khilali Chighatay; Khussaini; Shafikai Yarkin